Artificial Intelligence and Robotics in Minimally Invasive and Complex Surgical Procedures: A Systematic Review - Abdalla Osman, Eman Ibrahim; Mubarak Ismail, Manasik M. ElMurtada; Hassan Mukhtar, Mohamed Ahmed; Babiker Ahmed, Ahmed Umballi; Abd Elfrag Mohamed, Nihal Ahmed; Alamin Ibrahim, Ali Ahmed (Curēus (Palo Alto, CA), 2025)
Robotics and artificial intelligence (AI) are transforming surgery by improving patient outcomes, efficiency, and precision. The use of robotics in surgery tackles important issues, including surgical precision, minimally invasive procedures, and healthcare accessibility, as global healthcare systems embrace AI-driven technologies more and more. However, access gaps and ethical issues with automation continue to exist on a worldwide scale, calling for a fair discussion of these developments. The aim of this systematic review was to summarize the most recent literature on the role of AI and robotics in minimally invasive and complex surgical procedures. The study was conducted as per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We search for relevant studies across four different databases (PubMed, Scopus, Web of Science, and Google Scholar). We also restricted our search to 2024 to capture the most recent advancement only. We found 393 relevant studies, of which only 12 were included in this study upon assessing them with inclusion and exclusion criteria. The review ensures scientific rigor and openness by evaluating surgical specializations, AI technologies, and outcomes such as accuracy, recovery, and complications. The results show significant progress in AI-powered surgical systems, enhancing judgment, lowering surgical errors, and enabling individualized treatment plans. AI-enhanced visualization, real-time data processing, and automated robotic equipment are notable innovations that boost patient safety and procedure efficiency. The importance of these developments is emphasized throughout the discussion, especially with regard to developing minimally invasive procedures and increasing surgical capabilities for complex surgeries. However, obstacles to broad adoption are cited, including expenses, moral dilemmas, and the requirement for stringent training procedures.